Species diversity and size distribution of lift net catches in the coastal waters of Carocok Tarusan - Karina Theresia Simaibang; Lisna Lisna; Septy Heltria; Afriani Harahap; Ester Restiana Endang Gelis; Ainun Rohmawati Bareta (Jurnal Perikanan Terpadu, 2025)
Boat seine gear is a fishing gear is classified as a purse seine that has high productivity, resulting in a high composition of catches. The composition of fish species in the body of water is used to predict species diversity to show the number of individuals or different types of fish due to differences in size, shape, and quantity. In addition to diversity, size distribution also functions to show the growth rate of fish based on length frequency in a body of water. The purpose of this study was to analyze the diversity and size distribution of catches from boat seines in the Carocok Tarusan Coastal Waters. A survei method was used in this study. A purposive sampling method was used for the sampling. The study showed that the total catch of boat seine was 433.904 fish weighing 899,86 kg, which was divided into main catch (HTU) and bycatch (HTS). The number of HTU catches of payang was higher (92.51%) than that bycatch of 7,49%. The diversity index value in the Carocok Tarusan Coastal Waters was 0,37, the uniformity index was 0,12 and the dominance index was 0,86. It can be concluded that the results of the diversity and uniformity index are relatively low while the dominance index value is relatively high. The distribution of anchovy size as the main result of payang, which is 64,74% is considered worthy of being caught